Perubahan BunyiBahasa pada Tuturan Anak Balita di Paud Beriuk Tinjal Lombok Timur: Kajian Fonologi - Gobai, Afianci; Suparwa, I Nyoman; Putu Putra, Putu Putra (Stilistika : Journal of Indonesian Language and Literature; Vol 2 No 1 (2022): Volume 2 No. 1 Oktober 2022, 2022)
This research aims to knowing what language sounds are used and the process of sound change in the toddler speech. This research uses a qualitative approach. The data sources this research is five children aged two to three years. The method used in the data collection stage is the listening method with fishing technique, note-taking technique, engagement listening technique and recording technique. The method used to analyze the data is match method and agih method. The presentation of the result of data analysis is carried out by formal methods and informal methods. In this research it was found the acquisition of vowels and consonants in children aged 2-3 years has a different amount of sounds. At the age of two years and one month, get 16 vowels and consonants sounds, videlicet [c], [d], [h], [n], [m], [p], [t], [w], [y], [ a], [i], [u], [?], [?], [o], [?]; At the age of two years and three months, get 20 vowels and consonants sounds, videlicet [b], [c], [d], [g], [h], [k], [l], [m], [n], [ p], [t], [w], [y], [a], [i], [u], [?], [?], [o], [?]; and at the age of two years and five months, get 22 vowels and consonants sounds, videlicet [b], [c], [d], [g], [h], [j], [k], [l], [m], [n], [p], [s], [t], [w], [y], [a], [i], [u], [?], [?], [o], [?]; At the age of two years and eight months, there is 23 vowels and consonants soundas, videlicet [b], [c], [d], [g], [h], [j], [k], [l], [m], [n], [p], [s], [t], [w], [y], [a], [i], [u], [?], [?], [o], [?], [?]; whereas at the age of three years, get 23 vowels and consonant sounds, namely [b], [c], [d], [g], [h], [j], [k], [l], [m], [n], [p], [s], [t], [w], [y], [a], [i], [u], [?], [?], [o], [?], and [?]. The acquisition sounds which is still not mastered 2-3 years old children are [r] and [z].